1993
DOI: 10.1093/oxfordjournals.humrep.a138284
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy: Oocyte donation in menopausal women

Abstract: Oocyte donation was performed by in-vitro fertilization and embryo transfer in 82 women. The average age of the patients was 48 years (range 26-60), and 71 were over 40 years old, with an average follicle stimulating hormone (FSH) value of 74 +/- 14 IU and oestradiol concentration of 30 +/- 9 pg/ml. Overall 32 clinical pregnancies were achieved, of which 21 reached term, three are ongoing, and eight were lost (six miscarriages, one abruptio placentae, and one severe gestational proteinuria hypertension in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 0 publications
1
30
0
4
Order By: Relevance
“…In addition, an increase in the incidence of aneuploidy is well documented with increasing maternal age, particularly in humans [13,14]. Other studies have indicated that when embryos produced by young women were transferred into older women, the pregnancy rates were consistent with those of the young women [15,16]. Take together, the quality of the oocyte or embryo could be the primary cause of the decreased reproductive potential in the aging female.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, an increase in the incidence of aneuploidy is well documented with increasing maternal age, particularly in humans [13,14]. Other studies have indicated that when embryos produced by young women were transferred into older women, the pregnancy rates were consistent with those of the young women [15,16]. Take together, the quality of the oocyte or embryo could be the primary cause of the decreased reproductive potential in the aging female.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies, however, have indicated that when embryos produced from women <35 years of age were transferred into the uteri of women up to 59 years old, the establishment of pregnancy was not affected by age of the recipient (10,11). These studies suggest that it is the quality of the oocyte or embryo rather than the age of the recipient that is the primary cause contributing to the reproductive potential decrease in the aged female.…”
mentioning
confidence: 97%
“…Embryo cryo-preservation while still young provides the most successful option, freezing mature and immature oocytes and ovarian tissue with subsequent in-vitro maturation or autologous transplantation offer additional avenues (Ng and Ho 2007). The post-menopausal uterus does respond well when supported by steroid therapy and enable embryos to implant efficiently (Antinori et al 1993).…”
Section: Donation Of Genetic Materialsmentioning
confidence: 99%